2020
DOI: 10.1055/a-1221-5012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of EUS-RFA in pancreatic tumors: Is it ready for prime time? A systematic review and meta-analysis

Abstract: Background and study aims Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) can be used in patients with unresectable pancreatic ductal adenocarcinoma (PDAC). We performed a systematic review and meta-analysis to evaluate the efficacy of EUS-RFA in treatment of locally advanced unresectable PDAC and other pancreatic tumors. Patients and methods A comprehensive search was done of multiple electronic databases and conference proceedings including PubMed, EMBASE, Web of Science databases, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In this systematic review, which recruited several kinds of pancreatic tumor including pancreatic adenocarcinoma (n=38) pancreatic neuroendocrine neoplasm (n=53), metastasis to the pancreas (n=4) and other pancreatic lesions (n=41), reported adverse events rate associated with EUS-RFA at 14.7 %, of which, the abdominal pain was the most common event at 9.8%. 9 Based on our institutional experience and results from prior studies, neither death nor serious adverse events occurred from the result of the EUS-RFA procedure. In our experience, the only one adverse event that we had was mild pancreatitis which was successfully treated with conservative treatment.…”
Section: Efficacy Of Eus-rfa For Pancreatic Cancermentioning
confidence: 92%
See 1 more Smart Citation
“…In this systematic review, which recruited several kinds of pancreatic tumor including pancreatic adenocarcinoma (n=38) pancreatic neuroendocrine neoplasm (n=53), metastasis to the pancreas (n=4) and other pancreatic lesions (n=41), reported adverse events rate associated with EUS-RFA at 14.7 %, of which, the abdominal pain was the most common event at 9.8%. 9 Based on our institutional experience and results from prior studies, neither death nor serious adverse events occurred from the result of the EUS-RFA procedure. In our experience, the only one adverse event that we had was mild pancreatitis which was successfully treated with conservative treatment.…”
Section: Efficacy Of Eus-rfa For Pancreatic Cancermentioning
confidence: 92%
“…8 A recent systematic review of 38 patients with unresectable pancreatic cancer reported technical and clinical success rate at 100% (38/38) and (26/26). 9 The technical success was defined as a successful placement of the EUS-RFA probe into the target lesions, and the clinical success was defined as necrosis of target lesion by EUS-RFA. In this systematic review, which recruited several kinds of pancreatic tumor including pancreatic adenocarcinoma (n=38) pancreatic neuroendocrine neoplasm (n=53), metastasis to the pancreas (n=4) and other pancreatic lesions (n=41), reported adverse events rate associated with EUS-RFA at 14.7 %, of which, the abdominal pain was the most common event at 9.8%.…”
Section: Efficacy Of Eus-rfa For Pancreatic Cancermentioning
confidence: 99%
“…Another meta-analysis evaluated this technique for the treatment of different types of pancreatic tumors and showed a technical success of 100%, a clinical success of 91.5% and an overall adverse event rate of 14.6%, where abdominal pain was the most frequently reported[ 62 ]. Most available studies that have evaluated this technique are small-sized studies with fewer than 10 patients and uncontrolled protocols.…”
Section: Interventional Eus In Pancreatic Cancermentioning
confidence: 99%
“…A recently published systematic review and meta-analysis of 13 studies including 134 patients reported the technical success rate to be 100% and clinical success to be 92%. The pooled overall adverse event rates were 15%, with abdominal pain being the most reported at 9.8% [ 75 ].…”
Section: Endoscopic Treatmentsmentioning
confidence: 99%